2017
DOI: 10.4314/ahs.v16i4.24
|View full text |Cite
|
Sign up to set email alerts
|

Opiate withdrawal syndrome in buprenorphine abusers admitted to a rehabilitation center in Tunisia

Abstract: Background: Illicit use of high dosage buprenorphine has been well documented in several countries, including Tunisia. Objectives: The aim of this survey is to assess the buprenorphine withdrawal syndrome time course, and how it may be affected by the population characteristics among subjects admitted to a rehabilitation center in Tunisia. Methods: A prospective research has permitted study of the socio-demographic characteristics and assessment of buprenorphine withdrawal syndrome among 32 subjects admitted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Concerns associated with buprenorphine therapy include: 1. a series of active metabolites that are full MOR agonists (Moody et al, 2011;Häkkinen et al, 2012;Tompkins et al, 2014); 2. subversion for recreational purposes or to relive symptoms of dependence (Nigan et al, 1994;Eissenberg et al, 1996;Tompkins et al, 2014;Derbel et al, 2016), and 3. respiratory depression either in patients with compromised respiratory function, or when buprenorphine is combined with benzodiazepines (FDA, 2012(FDA, , 2018Schuman-Olivier et al, 2013;Jones and McAninch, 2015;Dowell et al, 2016;Hirschtritt et al, 2017). Critically, preclinical models can be used to assess these high risk circumstances.…”
Section: Rm1490 Comparison To Buprenorphinementioning
confidence: 99%
“…Concerns associated with buprenorphine therapy include: 1. a series of active metabolites that are full MOR agonists (Moody et al, 2011;Häkkinen et al, 2012;Tompkins et al, 2014); 2. subversion for recreational purposes or to relive symptoms of dependence (Nigan et al, 1994;Eissenberg et al, 1996;Tompkins et al, 2014;Derbel et al, 2016), and 3. respiratory depression either in patients with compromised respiratory function, or when buprenorphine is combined with benzodiazepines (FDA, 2012(FDA, , 2018Schuman-Olivier et al, 2013;Jones and McAninch, 2015;Dowell et al, 2016;Hirschtritt et al, 2017). Critically, preclinical models can be used to assess these high risk circumstances.…”
Section: Rm1490 Comparison To Buprenorphinementioning
confidence: 99%
“…The European Monitoring Centre for Drugs and Drug Addiction annual reviews have revealed large differences in OAT implementation and outcomes in different countries. 69 In some countries like Tunisia and Georgia 70,71 buprenorphine is not approved to treat OUD and drug use is criminalized. In contrast, some countries like Finland and Sweden have buprenorphine regulatory conditions similar to France but, diversion of buprenorphine has emerged as a F I G U R E 4 diagram of second-order articles by location.…”
Section: Different Representations Of Problems In Different Localesmentioning
confidence: 99%
“…; while Tunisian researchers report on opiate withdrawal syndrome in buprenorphine abusers admitted to a rehabilitation center 23 . The section ends with a rhetorical question: Does exercise alleviate depression related systemic inflammation in chronic obstructive pulmonary disease patients?…”
mentioning
confidence: 99%